Epidermolysis Bullosa and Its Role in Cervical Cancer: An Overview - Jugal Jaiswal (International Journal of Cell Biology and Cellular Functions, 2024)
Epidermolysis Bullosa is a group of uncommon genetic disorders that primarily affect the skin and mucous membranes. It is marked by severe skin fragility and the formation of blisters even after minor trauma. Traditionally, the focus of Epidermolysis Bullosa research has been on its dermatological manifestations, which include recurrent blistering, scarring, and the potential for infections due to the compromised skin barrier. However, recent advancements in Epidermolysis Bullosa research have shifted attention to its broader implications, particularly its potential link to certain types of cancer, with cervical cancer emerging as one of the most notable associations. Studies suggest that individuals with certain forms of Epidermolysis Bullosa, especially those with recessive dystrophic Epidermolysis Bullosa, may be at heightened risk for developing cancers, including cervical cancer. This increased susceptibility is thought to be due to chronic skin damage, prolonged inflammation, and the role of genetic mutations in Epidermolysis Bullosa that may contribute to an environment conducive to oncogenic processes. For instance, in recessive dystrophic Epidermolysis Bullosa, mutations in the collagen VII gene result in abnormal skin structures that could potentially trigger cellular pathways leading to malignancy. This article aims to investigate the mechanisms that contribute to the heightened risk of cervical cancer in individuals with Epidermolysis Bullosa. By examining the molecular pathways involved in Epidermolysis Bullosa and their intersection with carcinogenesis, it highlights how defective skin integrity and persistent tissue damage could contribute to the development of cervical cancer. Furthermore, the paper explores the risk factors specific to Epidermolysis Bullosa patients, emphasizing the need for regular cancer screenings and early detection in these vulnerable populations. Understanding these connections is essential for enhancing clinical care and creating preventive strategies for patients with Epidermolysis Bullosa.
Keywords: Epidermolysis Bullosa; Genetic; cell; cervical cancer; collagen VII